2019
DOI: 10.1017/jfm.2019.540
|View full text |Cite
|
Sign up to set email alerts
|

Swimming freely near the ground leads to flow-mediated equilibrium altitudes

Abstract: Experiments and computations are presented for a foil pitching about its leading edge near a planar, solid boundary. The foil is examined when it is constrained in space and when it is unconstrained or freely swimming in the cross-stream direction. It was found that the foil has stable equilibrium altitudes: the time-averaged lift is zero at certain altitudes and acts to return the foil to these equilibria. These stable equilibrium altitudes exist for both constrained and freely swimming foils and are independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 32 publications
16
53
2
Order By: Relevance
“…A similar conclusion was examined in the validation study of Lucas et al (2017). Recent work has shown that ground effects are not limited to accelerating swimming but are present in steady swimming as well (Kurt et al, 2019), suggesting that the presence of ground effects should not bias comparisons between the two swimming modes. Furthermore, using only sequences in which the animal remained in the laser sheet minimized possible ground effect discrepancies between sequences and treatments by ensuring that animals were filmed at the same height above the bottom (∼0.1 body lengths, bl; see below) for all sequences.…”
Section: Methodssupporting
confidence: 59%
“…A similar conclusion was examined in the validation study of Lucas et al (2017). Recent work has shown that ground effects are not limited to accelerating swimming but are present in steady swimming as well (Kurt et al, 2019), suggesting that the presence of ground effects should not bias comparisons between the two swimming modes. Furthermore, using only sequences in which the animal remained in the laser sheet minimized possible ground effect discrepancies between sequences and treatments by ensuring that animals were filmed at the same height above the bottom (∼0.1 body lengths, bl; see below) for all sequences.…”
Section: Methodssupporting
confidence: 59%
“…On the other hand, zooming into the problem of a single swimmer, despite the successes of Lighthill's theory to describe the mechanics of fish swimming [9], the ubiquitous problems of the interaction between a swimmer and its environment are out of its reach. This environment can be a wall, a substrate (a significant number of works have explored this problem in different contexts [10][11][12][13]), or another neighboring swimmer. The interactions between multiple swimmers may significantly impact the performance or cost of locomotion associated with fish schooling, as each swimmer moves in a non-uniform and unsteady flow created by its neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Kurt et al . (2019) recently performed experimental and numerical studies for a freely movable rigid fin in the lateral direction to identify a lateral equilibrium altitude for a zero when the fin was constrained in the horizontal direction. They showed that a stable equilibrium position of a freely swimming fin with a zero exists in the lateral direction, and the lateral position is similar to that of a laterally constrained fin with a zero .…”
Section: Resultsmentioning
confidence: 99%
“…As d/A head,l decreases, the fins show a negative due to a time-averaged angled jet away from the wall (not shown) formed by a deflected vortex pair (figure 2 b ), consistent with the jet deflection mechanism of Kurt et al . (2019). As d/A head,l decreases further ( d/A head,l < 2.5 for the leader and d/A head,l ≤ 3.0 for the follower), the sign of acting on the fins is positive due to the enhancement of a positive pressure between the fins and the wall (for example, see the pressure contours around the fins for 1W at t / T = 0.625 and 0.75 in figure 12), consistent with the quasi-static mechanism by Kurt et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation